Magnetic Properties and Mössbauer Study of Perovskite LaFeO3 and LaFe0.5Cr0.5O3. Issue 6 (2nd March 2022) - Xia, Puyue; Mo, Jiajun; Chen, Jiangbin; Liu, Min; Xia, Yanfang
Abstract : Herein, a citric acid combustion method is used to prepare LaFeO3 (LFO) and LaFe0.5 Cr0.5 O3 (LFCO). Stable and distorted perovskite structures are detected by X‐ray diffraction (XRD) patterns of both samples. Due to the substitution of chromium ions, Fe–Fe couplings are wholly disrupted, thus indicating the transition from a sextet to a singlet at room temperature. The M versus T curve of LFO exhibits two anomalous peaks related to Fe–O–Fe superexchange interactions. However, a quite different behavior is observed in LFCO. It reveals the negative irreversibility below 239 K and becomes paramagnetic above 269 K. The field‐cooled (FC) curve of LFCO is also simulated using the Monte Carlo method with Heisenberg model. Exchange coupling and anisotropy constants, which indicate some system properties, are calculated by applying the particle swarm algorithm fitting. The Néel temperature of LFCO is determined to be 80 K. Abstract : LaFeO3 is antiferromagnetic, whereas paramagnetic for LaFe0.5 Cr0.5 O3 at room temperature. Two anomalous peaks in M versus T curve of LaFeO3 are related to antiferromagnetic Fe–Fe couplings. However, the negative irreversibility of LaFe0.5 Cr0.5 O3 arises from the competition between Cr–O–Cr interactions and relevant anisotropy. The FC curve of LaFe0.5 Cr0.5 O3 is simulated by Monte Carlo method, which also calculates magnetic parameters.